2023
DOI: 10.2174/18749445-v16-e230320-2022-205
|View full text |Cite
|
Sign up to set email alerts
|

Growth Monitoring and Promotion and Index Development for Improved Child Health: A Scoping Review Using Rodgers Concept Analysis Framework

Abstract: Purpose: The purpose of this scoping literature review is to explore the breadth of the available literature, and identify knowledge gaps to inform future research through the use of Rodgers evolutionary concept analysis framework. The literature review also seeks to describe the key child indices developed and their characteristics so as to guide the development of a GMP index for improved child health in Zimbabwe. Methods: The keywords… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Having defined the GMPI as a measure of the quality of GMP activities has enabled GMP implementers to move away from the usual classifications which were based on the currently existing child health indexes such as weight-for-height. The scoping literature review by Moyo et al [23] identified a few indexes that have been used for the GMP of children. The most common indexes are the WHO Growth Standards that only assess nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having defined the GMPI as a measure of the quality of GMP activities has enabled GMP implementers to move away from the usual classifications which were based on the currently existing child health indexes such as weight-for-height. The scoping literature review by Moyo et al [23] identified a few indexes that have been used for the GMP of children. The most common indexes are the WHO Growth Standards that only assess nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers, through their scoping literature review [23], showed that not many child health-related indexes exist. Therefore, this new GMPI and its development have added to the body of existing knowledge.…”
Section: Discussionmentioning
confidence: 99%